Environmental Factors Influencing Macrophytes Assemblages in a Middle‐Sized Mediterranean Stream. (19th February 2015) - Manolaki, P.; Papastergiadou, E.
Abstract: The occurrence of aquatic plants was analysed in a medium‐sized river in Greece. There were three objectives. The first was to examine the macrophyte assemblage structure along the river. The identification and hierarchical structure of aquatic plant assemblages were analyzed using Bray–Curtis analysis. Taxa primarily responsible for the differences among the assemblages were identified using similarity percentage analysis. The second objective was to investigate whether habitat features have greater impact on aquatic plant assemblages than chemical parameters. Partial canonical correspondence analysis was used for partitioning the total variation of the biological response. The third objective was to further explore the relationships between hydrophytes (water‐supported plants) richness and water quality using linear regression model. The results showed that from the 86 macrophyte taxa recorded, the 25 were found to be primarily responsible for the differences among the macrophytic assemblages. Both geomorphological and physicochemical variables proved to be significant in the Monte Carlo permutation test. The 14 out of 19 geomorphological variables were statistically significant ( p <0.004) and included in the final canonical correspondence analysis model. From physicochemical variables, temperature, conductivity and water velocity were significant predictors of species distribution. Total macrophyte variation was divided into portions: (i) explained exclusively by geomorphological variables (34%); (ii) explained exclusively by physicochemical variables (3%); (iii) explained by both variables (52%); and (iv) unexplained (4%). Partitioning clearly revealed that macrophyte assemblage structure was strongly associated with geomorphological features. Τhe results indicated that hardness, DO and chl‐ a play a more prominent role in hydrophyte species richness at community level. Copyright © 2015 John Wiley & Sons, Ltd.